Diagnostic Accuracy of Delirium Assessment Tools Among Critically Ill Infant : A Systematic Review - Dewi Astika Rahmadhani; Risna Ningsih; Atik Setiawati; Siti Chodidjah; Nur Agustini; Mega Hasanul Huda (GLOBAL HEALTH SCIENCE GROUP, 2025)
Delirium is an acute change in neurologic function that can potentially lead to longterm impacts on children’s cognitive development and the quality of life. Infants under 12 months are particularly vulnerable because their cognitive and language abilities are not fully developed. Therefore, healthcare professionals need to enhance their knowledge of delirium symptoms, child development stages, and how to identify it in this age group to better detection and management. This study aims to evaluate the diagnostic accuracy of delirium assessment tools, namely the Cornell Assessment of Pediatric Delirium (CAPD), the Preschool Confusion Assessment Method for the ICU (psCAM-ICU), and the Sophia Observation Withdrawal Symptoms Pediatric Delirium (SOSPD), in detecting delirium in critically ill infants. This systematic review follows the PRISMA 2020 guidelines and includes a literature search in PubMed, Scopus, ProQuest, ScienceDirect, and Taylor & Francis from 2013 to 2023. Inclusion criteria consist of observational studies involving infants aged 0-11 months in ICU settings that utilized CAPD, psCAM-ICU, or SOSPD for delirium detection. The quality of the studies was assessed using the JBI Critical Appraisal Checklist for Studies Reporting Diagnostic Test Accuracy. Result : The analysis indicates that the SOSPD tool has a sensitivity ranging from 76.9% to 96.8% and specificity between 92% and 96.4%. The CAPD shows sensitivity from 87% to 94.1% and specificity from 88% to 98%. The psCAM exhibits sensitivity from 75% to 95% and specificity from 81% to 91%. The results demonstrate variability in accuracy depending on the age group and clinical condition of the children. Based on the research findings, psCAM is recommended as the most effective tool for detecting delirium in the infant population due to its ease of use and high accuracy. Early detection of delirium is crucial for enhancing clinical management and improving outcomes in critically ill infants.